Resident and Police Perceptions of the Neighborhood: Implications for Community Policing - Stein, Rachel E. (Criminal justice policy review, 2015)
The successful implementation of community policing programs is dependent on police and residents understanding the needs of their communities. Differences between resident and police perceptions can affect the success of crime prevention strategies. Much neighborhood research highlights residents’ perceptions of their neighborhoods; the perceptions of police officers are often not taken into account. The current research examines police and resident perceptions of three high crime neighborhoods in a Midwestern city in the United States. Results indicate residents and police have different interpretations of the neighborhoods. Resident perceptions of neighborhood measures are relatively consistent across the three neighborhoods. Police perceptions of their relationship with residents and the close-knit structure of the community, however, are more positive in the primarily White neighborhood that has an active crime prevention program. The findings suggest that what the officers see in the neighborhood is driving perceptions, while actual problems might play a secondary role.